Loading to failure of a 55 year old prestressed concrete bridge - Bagge, Niklas; Nilimaa, Jonny; Sas, Gabriel; Blanksvärd, Thomas; Elfgren, Lennart; Tu, Yongming; Carolin, Anders (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2015)
In order to provide relevant data for calibration and development of methods for assessment ofexisting bridges, a 55 year old posttensioned concrete bridge has been subjected to non-destructiveand destructive tests. The bridge, located in Kiruna, Sweden, was a 121 m long girder bridgecontinuous in five spans. The test programme included failure loading of the girders and slab,respectively, condition assessment of the post-tensioned cables and material tests. Moreover, twostrengthening systems, using carbon fibre reinforcing polymer (CFRP), were evaluated. In this paperthe experimental programme and some preliminary results are presented to give an insight to researchproject. Godkänd; 2015; 20141128 (nikbag)